1978
DOI: 10.1083/jcb.78.2.r23
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament protein is phosphorylated in the squid giant axon.

Abstract: Lasek and Hoffman (7) and Gilbert (1) have shown that the two major subunits of squid neurofilament protein (NFP) have molecular weights by SDS-PAGE of 2.0 x 105 and 6.0 • 104 daltons. The subunits of NFP were identified by purifying the intact neurofilaments away from the other major constituents of extruded axoplasm. Neurofilaments were identified by their characteristic fine structure as seen with the electron microscope. The standard methods developed to purify

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 8 publications
3
48
0
Order By: Relevance
“…Previous SDS-PAGE and Western blot studies identified two major NF proteins in the squid giant axon, a high molecular weight phosphorylated protein, NF 220, a low molecular protein, NF 60 (Brown and Lasek 1990;Cohen et al 1987;Pant et al 1978), and a dephosphorylated form of NF220, approximately 190 kD, found together with NF60 in the cell bodies in the GFL (Tytell et al 1990). Subsequent molecular cloning studies in our laboratory revealed that there were two low molecular weight NF mRNAs in the GFL, an abundant NF60 mRNA and a small amount of a NF70 mRNA, in addition to a higher molecular weight mRNA corresponding to NF 190, all of which were formed from a single gene by alternative splicing (Szaro et al 1991;Way et al 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Previous SDS-PAGE and Western blot studies identified two major NF proteins in the squid giant axon, a high molecular weight phosphorylated protein, NF 220, a low molecular protein, NF 60 (Brown and Lasek 1990;Cohen et al 1987;Pant et al 1978), and a dephosphorylated form of NF220, approximately 190 kD, found together with NF60 in the cell bodies in the GFL (Tytell et al 1990). Subsequent molecular cloning studies in our laboratory revealed that there were two low molecular weight NF mRNAs in the GFL, an abundant NF60 mRNA and a small amount of a NF70 mRNA, in addition to a higher molecular weight mRNA corresponding to NF 190, all of which were formed from a single gene by alternative splicing (Szaro et al 1991;Way et al 1992).…”
Section: Resultsmentioning
confidence: 99%
“…A different type of neurofilament dynamics is governed in part by the phosphorylation state of the long, highly charged C-terminal tail regions of NF-M and NF-H, which are peripherally situated on the filament and may correspond to the sidearms of neurofilaments [Pant et al, 1978;Sharp et al, 1982;Leterrier et al, 1982;Hirokawa et al, 19841. The phosphorylation of many sites on the tail domains, which is mediated by one or more neuron-specific cytoskeletonassociated kinases Runge et al, 1981;Shecket and Lasek, 19821, is delayed until after neurofilaments have entered the axon and continues as neurofilaments are transported [Glicksman et al, 1987;Oblinger, 1987;Nixon et al, 19871.…”
Section: Neurofilament Dynamicsmentioning
confidence: 99%
“…Recent observations that the major neurofflament proteins (NFPs) exhibit microheterogeneity (6, I0, 35, 36) and are modified by phosphorylation (35,40,56) indicate that neurofilament structure may be quite complex. Little is known, however, about the nature of this heterogeneity, the spatial organization of the several neurofilament protein forms within neurons and their processes, and whether the structural heterogeneity is related to functional complexity.…”
mentioning
confidence: 99%